Predictors of weight velocity in the first 6 months of life in a Rural block of West Bengal: A longitudinal study - Arista Lahiri; Arup Chakraborty (Wolters Kluwer Medknow Publications, 2019)
Background: Monthly weight gain (weight velocity) is important in early infancy, with several factors affecting and interacting within the healthy-born children. The current study aims to estimate on the effects of different factors on the trend of weight gain during the first 6 months of life. Methods: A longitudinal (repeated-measures) study was conducted on the 42 nonlow birth weight healthy children born in selected rural areas during December 2016. Infant feeding attitude, effective breastfeeding, timely feeding, and episodes of diarrheal illnesses were the major predictors along with the age of the children on the weight velocity in a sex-dependent repeated-measures analysis using Generalized Estimating Equations. Results: Mothers of the children were mostly below the mean age of 20.1 years (60.905%), majority being homemakers (71.429%). Majority (73.809%) had a better infant feeding attitude. The mean birth weight for male infants was 2.941 (±0.299) kg and females 2.938 (±0.352) kg. Age of the child, birth weight, timely feeding, and episodes of diarrheal illnesses had statistically significant effect on monthly weight gain. Feeding breast milk only proved advantageous for males. Conclusions: Effectively, only breastfeeding, timely feeding, and prevention of diarrheal episodes were the most important recommendations at the field level.